The Application of Good Governance Principles in The Management of State Owned Enterprises: A Case Study of The Alleged 2025 Pertamina Mega Corruption Scandal - Angelly Dechinta Lesawengen; Agustin Widjiastuti; Yeheskiel Benaya Entaren (International Journal Labs, 2026)
This research aims to analyze the application of good governance principles in the management of State-Owned Enterprises (BUMN), specifically PT Pertamina (Persero), and to assess the effectiveness of existing legal regulations in preventing mega-corruption practices. Indonesia, as a country of law, places the principles of transparency, accountability, responsibility, independence, and fairness as the foundation of public and state corporate governance. Although various legal instruments are available, such as Law Number 19 of 2003 concerning BUMN, the Limited Liability Company Law, and the Government Administration Law, the study shows a gap between normative provisions and management practices in the field, as reflected in the alleged mega-corruption case of PT Pertamina in 2025. The research methodology used is juridical-normative with a statutory, conceptual, and case study approach, prioritizing the analysis of legal doctrine, regulations, and court decisions as primary, secondary, and tertiary legal materials. The results of the study found that weak internal oversight systems, suboptimal audit mechanisms, political intervention, and conflicts of interest are the main factors contributing to the failure of implementing good governance principles in BUMN. This research recommends strengthening regulations, professionalizing corporate bodies, fostering a supportive legal culture, and establishing an independent oversight system to ensure transparent, accountable, and public-interest-oriented governance of state-owned enterprises. These findings are expected to serve as a basis for improving the legal framework and policies for managing state-owned enterprises in Indonesia, thereby preventing the recurrence of mega-corruption practices in the future.